Racial and Ethnic Differences in Heroin, Methamphetamine, and Cocaine Use, Treatment, and Mortality Trends in 3 National Data Sources-United States, 2010-2019 - Shearer, Riley D; Segel, Joel E; Howell, Benjamin A; Jones, Abenaa A; Khatri, Utsha G; Teixeira da Silva, Daniel; Vest, Noel; Winkelman, Tyler N A (Medical care, 2024)
As overdose deaths continue to rise, public health officials need comprehensive surveillance data to design effective prevention, harm reduction, and treatment strategies. Disparities across race and ethnicity groups, as well as trends in substance use, treatment, or overdose deaths, have been examined individually, but reports rarely compare findings across multiple substances or data sources. To provide a broad assessment of the overdose crisis, we describe trends in substance use, treatment, and overdose mortality across racial and ethnic groups for multiple substances. We conducted a longitudinal, cross-sectional analysis comparing trends. We identified self-reported use from the National Survey on Drug Use and Health, substance use treatment admissions from the Treatment Episode Data Set-Admissions, and overdose deaths from the CDC's Multiple Cause of Death files. We measured rates of substance use, treatment, and deaths involving heroin, methamphetamine, and cocaine among United States adults from 2010 to 2019. Heroin, methamphetamine, and cocaine use increased, though not all changes were statistically significant. Treatment admissions indicating heroin and methamphetamine increased while admissions indicating cocaine decreased. Overdose deaths increased among all groups: methamphetamine (257%-1,115%), heroin (211%-577%), and cocaine (88%-259%). Changes in rates of use, treatment, and death for specific substances varied by racial and ethnic group. Substance use, treatment, and overdose mortality changed considerably, though not always equivalently. Identifying diverging trends in substance-related measures for specific substances and racial and ethnic groups can inform targeted investment in treatment to reduce disparities and respond to emerging changes in the overdose crisis.